Concept maps as dynamic tools to increase students' understanding of knowledge and creative thinking - Rida Fironika Kusumadewi; Imam Kusmaryono (Universitas PGRI Madiun, 2022)
Concept maps are closely related to students' understanding of knowledge and creative thinking skills. This study aims to determine the effectiveness of concept maps as in increasing understanding of knowledge and creative thinking skills when students are involved in learning activities. The type of research method chosen is descriptive analysis. Research data were collected through (1) questionnaires, (2) concept map assessment rubrics, and (3) interviews. The results of the questionnaire were evaluated using the percentage technique. Students' answers to open-ended questions about the advantages and disadvantages of applying concept maps are summarized and analyzed descriptively. The results showed that most respondents stated that learning with concept maps was fully effective. Analysis of answers to questionnaires and open-ended questions cloncludes that concept maps are effective as a tool to improve students' understanding of knowledge and creative thinking skills that have implications for meaningful learning, student positive attitudes, and student academic achievement.